Factors Influencing Earnings Management : an Empirical Study on the Indonesian Stock Exchange - Nadira Widya Febrianti; Fajar Nurdin (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to analyze the effect of Tax Planning, Deferred Tax Expenses, and Tax Expenses on Earnings Management. The independent variables in this study are tax planning, deferred tax expense, and current tax expense, while the dependent variable is earnings management which is measured by capitalization rate as a proxy for the market value of equity. The population of this research is the consumption companies of the Food and Beverage Sub-Sector which are listed on the Indonesia Stock Exchange from 2011-to 2020. The sampling technique was purposive sampling. And obtained 12 companies. The type of data used is secondary data in the form of the company's annual financial statements obtained from the IDX website or company website. Data analysis using multiple linear regression test with the help of SPSS software version 24. The results of this study reveal that tax planning partially does not affect earnings management. Meanwhile, deferred tax expenses and current tax expenses partially affect earnings management. Simultaneously tax planning, deferred tax expense, and current tax expense affect earnings management. This third independent variable is useful for consideration and evaluation in conducting earnings management.